2019
DOI: 10.1186/s12985-019-1215-8
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Bemisia tabaci feeding behaviors caused directly and indirectly by cucurbit chlorotic yellows virus

Abstract: Background: Plant viruses can affect vector's behaviors in order to enhance viral transmission. Cucurbit chlorotic yellows virus (CCYV) (genus Crinivirus) is an emergent RNA plant virus and is transmitted specifically by biotypes B and Q of tobacco whitefly, Bemisia tabaci (Gennadius), in a semipersistent manner. Methods: We used the electrical penetration graph (EPG) to investigate the effect of CCYV on the feeding behaviors of B. tabaci biotypes B and Q. Results: CCYV could affect, both directly and indirect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 67 publications
0
28
0
Order By: Relevance
“…Plant viruses can manipulate vector insects by directly in uencing the feeding behavior. For example, B. tabaci carrying CCYV increased non-phloem probing and phloem salivation [24]. B. tabaci with TYLCV spend more time in phloem salivating and ingesting sap [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plant viruses can manipulate vector insects by directly in uencing the feeding behavior. For example, B. tabaci carrying CCYV increased non-phloem probing and phloem salivation [24]. B. tabaci with TYLCV spend more time in phloem salivating and ingesting sap [28].…”
Section: Discussionmentioning
confidence: 99%
“…CCYV seriously affected the yield and quality of melons in most parts of China and many Asian countries [21]. In our previous study, we found that CCYV had direct and indirect effects on the feeding behavior of B. tabaci, and the degree of in uence depends on the biological type (cryptic species) and sex of the insects [23,24]. However, there have been no reports about the effect of CCYV on the biological characteristics of B. tabaci.…”
Section: Introductionmentioning
confidence: 98%
“…The crinivirus cucurbit chlorotic yellows virus is transmitted by B. tabaci in a semi-persistent manner. Acquisition of the virus changed feeding behaviour in a biotype and sex dependent manner, but, overall, the results suggested an increased ability of the vector to transmit the virus [ 177 ]. Vector feeding behaviour can be modified to enhance the probability of transmission, as has been shown for some plant viruses belonging to the Bunyaviridae [ 117 , 118 ], a trait shared with animal infecting members of this virus family.…”
Section: Vector Behaviourmentioning
confidence: 99%
“…Similarly, plant viruses also directly influence vector feeding behavior to facilitate their transmission ( Mauck et al, 2018 ). Several reports show that infection of insect vectors with tomato spotted wilt virus (TSWV), tomato yellow leaf curl virus, rice dwarf virus, and southern rice black-streaked dwarf virus (SRBSDV) is associated with increased insect feeding frequency and prolongs salivation period ( Maris et al, 2004 ; Xu et al, 2014 ; Lei et al, 2016 ; Tan et al, 2017 ; Wang et al, 2018 ; Lu et al, 2019 ). Moreover, vector feeding behavior is correlated with sex and vector biotypes.…”
Section: Introductionmentioning
confidence: 99%